Postrift history of the eastern central Atlantic passive margin: Insights from the Saharan region of South Morocco. Issue 6 (29th June 2015) - Leprêtre, Rémi; Missenard, Yves; Barbarand, Jocelyn; Gautheron, Cécile; Saddiqi, Omar; Pinna‐Jamme, Rosella
Abstract: The passive margin of South Morocco is a low‐elevated passive margin. It constitutes one of the oldest margins of the Atlantic Ocean, with an Early Jurassic breakup, and little geological data are available concerning its postrift reactivation so far. We investigated the postrift thermal history of the onshore part of the margin with low‐temperature thermochronology on apatite crystals. Fission track and (U‐Th‐Sm)/He ages we obtained are significantly younger than the breakup (~190 Ma). Fission track ages range from 107 ± 8 to 175 ± 16 Ma, with mean track lengths from 10.7 ± 0.3 to 12.5 ± 0.2 µm. (U‐Th‐Sm)/He ages range from 14 ± 1 to 185 ± 15 Ma. Using inverse modeling of low‐temperature thermochronological data, we demonstrate that the South Moroccan continental margin underwent a complex postrift history with at least two burial and exhumation phases. The first exhumation event occurred during Late Jurassic/Early Cretaceous, and we attribute this to mantle dynamics rather than to intrinsic rifting‐related processes such as flexural rebound. The second event, from Late Cretaceous to early Paleogene, might record the onset of Africa/Europe convergence. We show a remarkably common behavior of the whole Moroccan passive margin during its early postrift evolution. The present‐day differences result from a segmentation of the margin domains due to the Africa/Europe convergence. Finally we propose that varying retained strengths during rifting and also the specific crustal/lithospheric geometry of stretching explain the difference between the topographical expressions on the continental African margin compared to its American counterpart. Key Points: South Moroccan passive margin has a polyphased Mesozoic‐Cenozoic thermal history An early postrift event controls the topographic evolution of the whole margin Lithospheric structure and rifting process control the early margin topography